2021
DOI: 10.1093/gigascience/giab026
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput microscopy reveals the impact of multifactorial environmental perturbations on colorectal cancer cell growth

Abstract: Background Colorectal cancer (CRC) mortality is principally due to metastatic disease, with the most frequent organ of metastasis being the liver. Biochemical and mechanical factors residing in the tumor microenvironment are considered to play a pivotal role in metastatic growth and response to therapy. However, it is difficult to study the tumor microenvironment systematically owing to a lack of fully controlled model systems that can be investigated in rigorous detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Caco-2 cells seem to be more sensitive to our compounds compared with HCT-116 cells, and this result is in agreement with chemosensitivity properties of the two lines [35].…”
Section: Anticancer Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…Caco-2 cells seem to be more sensitive to our compounds compared with HCT-116 cells, and this result is in agreement with chemosensitivity properties of the two lines [35].…”
Section: Anticancer Activitysupporting
confidence: 87%
“…Both cell lines are models of colorectal adenocarcinoma; however, each cell line represents diferent histological grade of colon cancer. Caco-2 is a model of less metastatic, less invasive, and more diferentiated colon cancer cells; however, HCT-116 is known to be a poorly diferentiated and highly invasive cell line, and it is one of the higher chemoresistant colon cell lines [35].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In addition, and just as explained for Caco‐2 cells, the mechanical behavior of the hydrogels is a relevant parameter. Stiffer substrates are known to lead to a higher cell proliferation [ 42 ] and in our case where Young's Moduli sharply rises from 2.1 kPa in DG0‐DG0 hydrogels to 11.6 kPa for PBS‐DG0, it is not surprising that HCT‐116 cells better proliferated on the latter ones. This specific biological response as a function of the hydrogel stiffness highlights how mechanics and biological properties are highly correlated.…”
Section: Resultsmentioning
confidence: 57%
“…Colonic adenocarcinoma cells attenuated to hypoxia produce smaller tumors than control cells [25]. Chiang CT demonstrated that the growth of highly aggressive colorectal cancer is affected by oxygen levels, as well as response to chemotherapy in which hypoxia has a protective effect against oxaliplatin-induced cytotoxicity in the plastics and liver extracellular matrix used [28].…”
Section: Non-cellular Componentsmentioning
confidence: 99%